Analisis Pelatihan Kewirausahaan Terhadap Motivasi Wirausaha Muda Oleh Dinas Kepemudaan, Olahraga, Kebudayaan dan Pariwisata Kota Cirebon - nunung nurnilasari (Exchall: Economic Challenge, 2021)
The training program for young entrepreneurs carried out by the City of Culture and Tourism Youth Youth Office for the first time on February 27, 2018, through this program is expected to provide motivation to young entrepreneurs who take part in the training. The training is useful for entrepreneurs who have started and who want to start a business, this research began from the first time it was held until the end of July 2018. The method used in this research is descriptive research method with associative type which is research that collects information from a sample by asking through questionnaires or interviews so that later can describe whether there is a relationship between entrepreneurship training on entrepreneurial motivation. After the data is processed with values ​​or figures that can be calculated systematically using systematic calculations, this research is quantitative in nature. Data from this study were obtained by distributing questionnaires to 58 respondents who were sampled. The results of the correlation coefficient study (r = 0.414) indicate that training entrepreneurship has a moderate relationship to entrepreneurial motivation. Because there are many factors that influence motivation such as venture capital, the environment and the entrepreneur himself, besides that this training is the first time held by the Youth Culture and Tourism Office of Cirebon City. Keywords: Entrepreneurship and Motivation Training